Grazing Pressure of Cattle on Mixed Pastures at Coal Mine Land Reclamation - T P Daru; S Hardjosoewignjo; L Abdullah; Y Setiadi; . Riyanto (Media Peternakan, 2012)
The objective of the research was to determine the grazing pressure in mix pasture of signal grass (Brachiaria decumbens) and puero (Pueraria phaseoloides) at coal mining reclamation. The experiment was arranged by randomized block design consisted of 5 stocking rate treatments, those were 12.56, 19.63, 28.26, 38.47, and 50.24 m2.animal-1.d-1 which were equal to length of tether rope of 2.0, 2.5, 3.0, 3.5, and 4.0 m, respectively. The rotation system was applied by modifying the tether. Each rotation period was 30 d of three-rotation period. Result of this experiment showed that average daily gain (ADG) was different (P2.animal-1.d-1 and decreased linearly with increasing length of rope from 254.29 to 100.17 kg.ha-1. Maximum dry matter consumption was achieved at length of tether rope of 3.32 m or grazing area 34.61 m2.animal-1.d-1. Average dry matter yield in this experiment was 235.39 g.m-2.d-1 or 2.35 ton.ha-1.mo-1. Botanical composition of signal grass, puero, and weeds before and after grazing was change with grazing pressure.